Does the source matter? Phenolic compounds and antioxidant activity from mycelium in liquid medium, wild and cultivated fruiting bodies of the neotropical species ganoderma tuberculosum - Campi, Michelle (2023)
As a continuation of the study of the biologically active compounds of native neotropical Ganoderma species in Paraguay, the content of total phenolic compounds, total antioxidants and percentage of antioxidant activity of the fractions extracted with ethanol, hexane, diethyl ether, ethyl acetate and water of mycelium in liquid medium, wild and cultivated fruiting bodies of G. tuberculosum, were analyzed. Biologically active compounds were highest in the diethyl ether fractions of wild fruiting bodies, 126.49 ± 4.19 mg. (GAE) g-1 (milligrams of Gallic acid equivalent per grams of crude extract), antioxidant compounds content of 130.94 ± 5.302 mg .g-1 AAE (milligrams of Ascorbic acid equivalent per grams of crude extract) and activity percentage of 70.93% compared to 67.39 ± 1.5 mg. (GAE) g-1, 48.37 ± 0.73.g-1 AAE and 45.63% antioxidant activity. According to the values obtained in the present study, the fruiting body of Ganoderma tuberculosum is a promising source of antioxidant compounds for the food industry.